A systematic review of vital events tracking by community health agents. Issue 1 (1st January 2019) - Nichols, Erin K.; Ragunanthan, Nina W.; Ragunanthan, Braveen; Gebrehiwet, Hermon; Kamara, Karim
ABSTRACT: Background : Efforts to improve national civil registration and vital statistics (CRVS) systems are focusing on transforming traditionally passive systems into active systems that have the ability to reach the household level. While community health agents remain at the core of many birth and death reporting efforts, previous literature has not explored elements for their successful integration into CRVS efforts. Objective : To inform future efforts to improve CRVS systems, we conducted a systematic review of literature to understand and describe the design features, resulting data quality, and factors impacting the performance of community health agents involved in tracking vital events. Methods : We reviewed 393 articles; reviewers extracted key information from 58 articles meeting the eligibility criteria: collection of birth and/or death information outside of a clinic environment by a community agent. Reviewers recorded information in an Excel database on various program aspects, and results were summarized into key themes and topic areas. Results : The majority of articles described work in rural areas of Africa or South-East Asia. Nearly all articles (86%) cited some form of household visitation by community health agents. Only one article described a process in which vital events tracking activities were linked to official vital events registers. Other factors commonly described included program costs, relationship of community agents to community, and use of mobile devices. About 1/3 of articles reported quantitative information on performance and quality of vital events data tracked; various methods were described for measuring completeness of reporting, which varied greatly across articles. Conclusions : The multitude of articles on this topic attests to the availability of community health agents to track vital events. Creating a programmatic norm of integrating with CRVS systems the vital events information collected from existing community health programs has the potential to provide governments with information essential for public health decision-making.